Trypanosoma cruzi infected mice exhibit follicular cytotoxic cd8+ t cells which condition b cell differentiation response in vitro - Gazzoni, Yamila Natali (2022)
Fil: Gazzoni, Yamila Natali. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas; Argentina